Keanekaragaman Diptera kanopi pada empat tipe penggunaan lahan berbeda di Jambi, Sumatra, Indonesia: The diversity of dipteran canopy on the four different land use types in Jambi, Sumatra, Indonesia - Ulfa Ulinnuha; Damayanti Buchori; Jochen Drescher; Stefan Scheu; Rizky Nazarreta; Kasmiatun; Paramita Hayu Widhyastuti; Akhmad Rizali; Purnama Hidayat (Perhimpunan Entomologi Indonesia, 2026)
Rainforest conversion into monoculture plantations has decreased tree canopy cover and insect diversity, including Diptera. Diptera is a group of insects that play a crucial role in maintaining the balance of ecosystems. This study aimed to assess the impact of forest conversion to plantations on the diversity and composition of Diptera across four landuse types in Jambi, Sumatra. Diptera sampling was conducted using canopy fogging in two landscapes: Bukit Duabelas National Park and Harapan Rainforest. In each landscape, four land use types were determined: forest, jungle rubber, rubber plantation, and oil palm plantation. A total of 13,513 Diptera individuals were collected, representing 39 families, 169 genera, and 399 species. The dominant family is Cecidomyiidae, and the dominant species is Procontarinia sp. 01. The highest abundance and species richness was found in forest, followed by jungle rubber. The lowest abundance was found in oil palm plantations, while the lowest species richness was found in rubber plantations. ANOVA test results indicated that different land use type significantly influenced Diptera abundance and species richness, whereas landscape had no significant effect. Diptera composition was influenced by land use type, landscape, and the interaction between land use type and landscape. Diptera composition in forest and jungle rubber showed the highest similarity, while the lowest similarity was in forest and oil palm plantation. This composition change was driven by species turnover. In addition, land conversion also caused a shift in dominance, with forests dominated by Cecidomyiidae, then dominance shifted to Ceratopogonidae in monoculture plantations.